2023-0107 Cross-border infrastructure projects The European Investment Bank's role in cross-border infrastructure projects (European Investment Bank, 2023)
Cross-border infrastructure projects are fixed-asset investments that physically link two or more countries via infrastructure, including digital infrastructure, enabling the flow of people, goods, commodities or data. They provide enormous long-term economic and social benefits and are vital to the functioning of the European Union's single market.A key factor that differentiates cross-border infrastructure projects from typical projects within a single country is their scale and complexity, as they very often span difficult terrain across borders, and involve two or more countries instead of just one. The greater complexity inherent in such projects means that they typically face several barriers.This report takes an in-depth look at these barriers, including those related to regulatory uncertainty, fragmentation, and complexity; as well as asymmetries in demand and prioritisation; and the complexities involved in coordinating funding sources. The report also showcases a number of case studies that demonstrate the European Investment Bank's vast experience in the area and explain why it is a unique centre of expertise for cross-border projects.